Bauran Pemasaran 7P dalam Pengembangan Usaha Gula Aren pada Kelompok Tani Hutan di Kawasan Hutan Desa Turu Adae - Makkarennu; Syahidah; Yumeina, Diyah; Amelia Thayeb, Diva; Maryam, Nevianti; Hasannudin, Dian Ayu Lestari; Irnasari (Fakultas Kehutanan, Universitas Hasanuddin, 2024)
This study analyzes the application of the 7P marketing strategy mix to palm sugar products in Turu Adae Village, Ponre Sub-district, Bone Regency. Palm sugar, produced from palm tree sap, is a traditional product with great potential but faces challenges in marketing. This study aims to analyze the components of the marketing mix, namely product, price, place, promotion, people, process, and physical evidence, and their impact on product competitiveness. The research method involved observation, interviews, and a literature study involving the entire population of palm sugar farmers involved in production. The results showed that although Batok palm sugar products still maintain traditional methods without modern packaging, these products excel in terms of authenticity and quality. Although batok palm sugar products maintain traditional methods without modern packaging, there are opportunities for improvement through packaging innovation, expansion of distribution channels, and more effective promotion both offline and online. In addition, attention to efficient production processes and improved human resource skills can increase product competitiveness. With proper implementation of the 7P marketing mix, palm sugar businesses in Turu Adae Village have the potential to grow and compete in a wider market.